Overall Efficiency Improvement of a Dual Active Bridge Converter Based on Triple Phase-Shift Control - Garry Jean-Pierre; Necmi Altin; Ahmad El Shafei; Adel Nasiri (Energies, 2022)
This paper proposes a control scheme based on an optimal triple phase-shift (TPS) control for dual active bridge (DAB) DC–DC converters to achieve maximum efficiency. This is performed by analyzing, quantifying, and minimizing the total power losses, including the high-frequency transformer (HFT) and primary and secondary power modules of the DAB converter. To analyze the converter, three operating zones were defined according to low, medium, and rated power. To obtain the optimal TPS variables, two optimization techniques were utilized. In local optimization (LO), the offline particle swarm optimization (PSO) method was used, resulting in numerical optimums. This method was used for the low and medium power regions. The Lagrange multiplier (LM) was used for global optimization (GO), resulting in closed-form expressions for rated power. Detailed analyses and experimental results are given to verify the effectiveness of the proposed method. Additionally, obtained results are compared with the traditional single phase-shift (SPS) method, the optimized dual phase-shift (DPS) method, and TPS method with RMS current minimization to better highlight the performance of the proposed approach.